Insights from Dysregulated mRNA Expression Profile of β-Cells in Response to Proinflammatory Cytokines. (22nd January 2022) - Wang, Zhen; Huang, Kunlin; Xu, Jing; Liu, Jia; Zheng, Ying
Abstract : Type 1 diabetes mellitus (T1DM) is a chronic autoimmune disease that is characterized by autoimmunity and its mediated β -cell damage. Chronic exposure of β -cells to proinflammatory cytokines is known to regulate the expression of many genes, subsequently resulting in the impairment of some signaling pathways involved with insulin production and secretion and/or β -cell apoptosis. In our study, RNA sequencing technology was applied to identify differentially expressed mRNAs in MIN6 cells treated with a mix of cytokines, including IL-1 β, TNF- α, and IFN- γ . The results showed 809 upregulated and 946 downregulated protein-coding mRNAs in MIN6 cells upon the stimulation of cytokines. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) biological pathway analyses were performed to predict the functions of dysregulated genes. The networks of circRNA-mRNA were constructed between differentially mRNAs and dysregulated expressed circRNAs in our previous study. In addition, we selected 8 dysregulated mRNAs for further validation by quantitative real-time PCR. The RNA sequencing data showed 809 upregulated and 946 downregulated protein-coding mRNAs. GO analysis showed that the top 10 significant "biological processes, " "cellular components, " and "molecular functions" for upregulated mRNAs include "immune system process, " "inflammatory response, " and "innate immune response" and the top 10 for downregulated mRNAs include "cell cycle, " "mitotic cytokinesis, " and "cytoplasm." KEGG analysis showed that these differentially expressed genes were involved with "antigen processing and presentation, " "TNF signaling pathway" and "type 1 diabetes, " "cell cycle, " "necroptosis, " and "Rap1 signaling pathway." We also constructed the networks of differentially expressed circRNAs and mRNAs. We observed that upregulated circRNA 006029 and downregulated circRNA 000286 and 017277 were associated with the vast majority of selected dysregulated mRNAs, while circRNA 013053 was only related to the protein-coding gene, Slc7a2 . To the summary, these data indicated that differentially expressed mRNAs may play key or partial roles in cytokine-mediated β -cell dysfunction and gave us the hint that circRNAs might regulate mRNAs, thereby contributing to the development of T1DM. The current study provided a systematic perspective on the potential functions and possible regulatory mechanisms of mRNAs in proinflammatory cytokine-induced β -cell destruction.